Branch-duct intraductal papillary mucinous neoplasm: a retrospective study on neoplastic risk after 5 years of surveillance - Marie-Pier Bachand; Mohamed-Anas Chennouf; Mandy Malick; Annie Beaudoin (Journal of Pancreatology)
Objectives:. Long-term surveillance of branch-duct intraductal papillary mucinous neoplasms (BD-IPMN) remains controversial, particularly regarding cysts follow-up >5 years. The primary endpoint of this study was to assess the risk of malignant transformation of presumed BD-IPMN during follow-up and identify clinical and morphological predictors of malignancy. Methods:. We performed a retrospective analysis of data from all patients with a presumed BD-IPMN diagnosis at the CIUSSS de l’Estrie CHUS, from 2004 to 2018. Results:. The final database included 380 patients with presumed BD-IPMN with a median follow-up of 43.9 months (interquartile range [IQR] 28.6–73.3 months). Mean age at diagnosis was 65.5 years [27–90], 159 patients (42.8%) were male and 17 patients (4.5%) underwent resection of their lesion during their surveillance period. In our cohort, 132 patients (34.7%) had a follow-up of >5 years. Overall risk of malignancy was 2.1% [0.9%–4.1%]. During follow-up, neoplastic transformation was observed in 2 of 132 patients (1.5%) surveilled >5 years. Malignancy was significantly associated with cyst growth >2.5 mm/y (57.1% vs 5.8%; P < .001) dilated MPD (71.4% vs 4.9%; P < .001), solid component (71.4% vs 1.3%; P < .001), positive cytology (37.5% vs 0.5%; P < .001), development of high-risk stigmatas (87.5% vs 1.9%; P < .001), or worrisome features (87.5% vs 23.9%; P < .001) during follow-up and symptoms of jaundice (25% vs 0.5%; P = .002) and abdominal pain (50% vs 9.4%; P = .005). Conclusion:. While overall malignancy risk remains low in presumed BD-IPMN, continuous surveillance should be pursued after 5 years in surgically fit individuals, particularly in patients who develop our identified risk factors.